Graphene nanosheets‐Inconel 718 nanocomposites fabricated by spark plasma sintering of in‐situ grown vertically standing graphene nanosheets‐Inconel 718 powders. (29th May 2019) - Chen, Dongsheng; Zhou, Haitao; Tian, Ye; Luo, Fei; Liu, Dabo; Luo, Bingwei
Abstract : The present work reports a mechanical improvement in nickel‐based nanocomposites reinforced by in‐situ grown graphene nanosheets (GNSs). First, vertically standing GNSs (VSGNSs) were grown on Inconel 718 alloy (718) powders by plasma‐enhanced chemical vapour deposition. Then these powders were used to fabricate GNSs‐718 nanocomposites by using spark plasma sintering method. The microstructure and mechanical properties of the nanocomposites were investigated by Raman spectroscopy, scanning electron microscopy, transmission electron microscopy and tensile tests. Testing results showed that three‐dimensional net structured VSGNSs were in‐situ grown on surfaces of 718 powders. GNSs‐718 nanocomposites exhibited homogeneously dispersed GNSs, which distributed mainly along grain boundaries. Transmission electron microscopy indicated that there were clean and strong interfaces between GNSs and nickel‐based matrix. Compared to the unreinforced 718 alloy, GNSs‐718 nanocomposites showed increased strength and elongation. The relevant strengthening mechanisms involved in GNSs‐718 nanocomposites were discussed.